Math Problem Statement

Find the matrix C using the formula: C = A^2 - (AB)^T + 3E, given matrices A = [[5, -6], [0, -1]] and B = [[-1, 1], [3, 2]].

Solution

We are given two matrices AA and BB, and the task is to find matrix CC, which is given by the formula:

C=A2(AB)T+3EC = A^2 - (AB)^T + 3E

Where:

  • A2A^2 is the square of matrix AA (i.e., A×AA \times A),
  • (AB)T(AB)^T is the transpose of the product of matrices AA and BB,
  • EE is the identity matrix of the same size as AA and BB.

Let's break down the problem:

Step 1: Define the matrices

Matrix AA and BB are:

A=(5601),B=(1132)A = \begin{pmatrix} 5 & -6 \\ 0 & -1 \end{pmatrix}, \quad B = \begin{pmatrix} -1 & 1 \\ 3 & 2 \end{pmatrix}

Step 2: Calculate A2A^2

First, we find the square of matrix AA, i.e., A×AA \times A.

A2=(5601)×(5601)A^2 = \begin{pmatrix} 5 & -6 \\ 0 & -1 \end{pmatrix} \times \begin{pmatrix} 5 & -6 \\ 0 & -1 \end{pmatrix}

A2=(5×5+(6)×05×(6)+(6)×(1)0×5+(1)×00×(6)+(1)×(1))A^2 = \begin{pmatrix} 5 \times 5 + (-6) \times 0 & 5 \times (-6) + (-6) \times (-1) \\ 0 \times 5 + (-1) \times 0 & 0 \times (-6) + (-1) \times (-1) \end{pmatrix}

= \begin{pmatrix} 25 & -24 \\ 0 & 1 \end{pmatrix}$$ ### Step 3: Calculate $$AB$$ Next, we compute the product of matrices $$A$$ and $$B$$, i.e., $$A \times B$$. $$AB = \begin{pmatrix} 5 & -6 \\ 0 & -1 \end{pmatrix} \times \begin{pmatrix} -1 & 1 \\ 3 & 2 \end{pmatrix}$$ $$AB = \begin{pmatrix} 5 \times (-1) + (-6) \times 3 & 5 \times 1 + (-6) \times 2 \\ 0 \times (-1) + (-1) \times 3 & 0 \times 1 + (-1) \times 2 \end{pmatrix}$$ $$AB = \begin{pmatrix} -5 + (-18) & 5 + (-12) \\ 0 + (-3) & 0 + (-2) \end{pmatrix} = \begin{pmatrix} -23 & -7 \\ -3 & -2 \end{pmatrix}$$ ### Step 4: Calculate $$(AB)^T$$ Now, we take the transpose of matrix $$AB$$. The transpose of a matrix is obtained by swapping its rows with its columns. $$(AB)^T = \begin{pmatrix} -23 & -7 \\ -3 & -2 \end{pmatrix}^T = \begin{pmatrix} -23 & -3 \\ -7 & -2 \end{pmatrix}$$ ### Step 5: Add the identity matrix $$3E$$ Since $$A$$ and $$B$$ are 2x2 matrices, the identity matrix $$E$$ is: $$E = \begin{pmatrix} 1 & 0 \\ 0 & 1 \end{pmatrix}$$ Multiplying by 3: $$3E = 3 \times \begin{pmatrix} 1 & 0 \\ 0 & 1 \end{pmatrix} = \begin{pmatrix} 3 & 0 \\ 0 & 3 \end{pmatrix}$$ ### Step 6: Calculate matrix $$C$$ Finally, we combine the results to find matrix $$C$$. $$C = A^2 - (AB)^T + 3E$$ Substitute the matrices: $$C = \begin{pmatrix} 25 & -24 \\ 0 & 1 \end{pmatrix} - \begin{pmatrix} -23 & -3 \\ -7 & -2 \end{pmatrix} + \begin{pmatrix} 3 & 0 \\ 0 & 3 \end{pmatrix}$$ First, subtract: $$\begin{pmatrix} 25 & -24 \\ 0 & 1 \end{pmatrix} - \begin{pmatrix} -23 & -3 \\ -7 & -2 \end{pmatrix} = \begin{pmatrix} 25 - (-23) & -24 - (-3) \\ 0 - (-7) & 1 - (-2) \end{pmatrix} = \begin{pmatrix} 48 & -21 \\ 7 & 3 \end{pmatrix}$$ Now, add $$3E$$: \[ C = \begin{pmatrix} 48 & -21 \\ 7 & 3 \end{pmatrix} + \begin{pmatrix} 3 & 0 \\ 0 & 3 \end{pmatrix} = \begin{pmatrix} 48 + 3 & -21 +

Ask a new question for Free

By Image

Drop file here or Click Here to upload

Math Problem Analysis

Mathematical Concepts

Matrix Multiplication
Matrix Transposition
Identity Matrix

Formulas

C = A^2 - (AB)^T + 3E
A^2 = A * A
(AB)^T = Transpose(A * B)
3E = 3 * Identity Matrix

Theorems

-

Suitable Grade Level

Grades 10-12